The Shift of Identity from Subterranean Space to Urban Space in Ralph Ellison’s Invisible Man - BOUCHERIA , FAIZA; Noureddine GUERROUDJ (Université de Laghouat , Bibliothèque centrale, 2018)
The attempt to come to terms with the meaning of space and identity, both literally and metaphorically, has become a major concern in literary studies. This dissertation explores the representations of displacement and divided identity from the point of view of Black American novelist. Space is regarded as the physical element of the events occurring in literary texts, that is to say that any artistic creation is accompanied by its own space being real or fictional. The present thesis presents a critical study of how space contributes in shaping the identity. Space and identity are inextricably bound to one another. The two are co-produced as people come to identify with where they live, shape it, however modestly, and are in turn shaped by their environments, creating distinctive environmental autobiographies, the narratives we hold from the memories of those spaces and places that shaped us. Exploring the relationship between space and identity deepens our understandings of identity formation and the role of place in social and psychological development. The bonds between space and identity can influence social formations, cultural practices, and political actions. It may be seen, for instance, in the efforts of groups of emigrants to establish roots in their new homes through the planting of particular tree species or architectural ornamentation In Invisible Man Ralph Ellison introduced two different spaces. The upground space in which the main character struggles to find his place in society. The narrator has rejected his own blackness. He has spent most of the novel trying to become white. The underground cave where the protagonist is retreated into himself to think out his identity, to come to some self-understanding. Here, alone, apart from those who try to force identity on him, he is able to arrive at some genuine self-knowledge. The cave is a place of contemplation, a place to grow a new skin and be protected from the harsh realities of the outside world until he is strong enough to go outside.